Awake thoracic epidural anesthesia for uniportal video-assisted thoracoscopic pleural decortication: A prospective randomized trial - Mohamed Rabeea; Esam Abdalla; Hussein Elkhayat; Fatma Nabil (Egyptian Journal of Anaesthesia, 2022)
Background Recently, video-assisted thoracoscopic surgery has replaced open thoracotomies. These surgeries are commonly done under general anesthesia with one-lung ventilation. The goal of this trial was to evaluate patient and surgeon satisfaction of awake uniportal video-assisted thoracoscopic pleural decortication under thoracic epidural anesthesia as an alternative to general anesthesia.Methods This prospective randomized trial included 66 patients who underwent uniportal video-assisted thoracoscopic pleural decortication. Patients were distributed into two equal groups: awake under thoracic epidural anesthesia (group TEA) and under general anesthesia (group GA).Results Patient satisfaction was significantly different between both groups (P < 0.039), as group TEA had higher percentage of the patients who described the procedure as unsatisfactory (33.3%) versus group GA (6.7%). Surgeon satisfaction was, also, better in group GA (P < 0.001).Conclusion Despite being technically applicable, this study showed that awake uniportal video-assisted thoracoscopic pleural decortication under thoracic epidural offers less patient and surgeon satisfaction compared to the same surgical procedure under general anesthesia.Clinical trials registry This trial is registered in ClinicalTrials.gov (NCT03902470).